A load-balanced algorithm for Internet Gateway placement in Backbone Wireless Mesh Networks - Mohammed, Najib Ahmed; Othman, Mohamed (Elsevier BV, 2024)
The placement of Internet Gateways (IGWs) is crucial in designing Backbone Wireless Mesh Networks (BWMNs) as it establishes the connection between the BWMN and the wired backbone. Efficient placement ensures high-bandwidth network coverage and utilization of the BWMN architecture. Despite considerable research efforts devoted to the IGW placement problem in WMNs, further research is still needed to tackle IGW reduction, improve Quality of Service (QoS), and achieve load balancing among IGWs and Wireless Mesh Routers (WMRs). In this paper, we propose a Load-balanced Algorithm for IGW placement in BWMN to achieve high-bandwidth network coverage while satisfying QoS constraints. The algorithm distributes WMRs among IGWs based on their location and computation degree, considering the load balance between IGWs and WMRs in each cluster. Experimental results demonstrate that our algorithm outperforms existing algorithms in terms of the number of IGWs placed in various scenarios. Our algorithm achieves an impressive reduction of more than 20 in the number of IGWs required in small typologies, and the improvement further escalates in larger topologies. To accomplish this, we utilize the innovative IGW Reallocation() algorithm, which accurately calculates the load ratio for each WMR within each cluster, facilitating the selection of the most suitable WMR to be designated as the new IGW. Additionally, our algorithm effectively addresses traffic load balancing for both IGWs and the entire network system by skillfully leveraging the relay links and delay hops present within WMRs forming the clusters. The outcomes of our research conclusively demonstrate that our Load-balanced Algorithm significantly enhances IGW placement efficiency, network coverage, and traffic load balancing, leading to improved performance, scalability, and a noteworthy contribution to the design and optimization of BWMNs.